Circulating interleukin 6 during a continuous infusion of tumor necrosis factor and interferon gamma (The Rockefeller University Press, 1989)
Plasma samples obtained from patients receiving a 24-h continuous infusion of human recombinant (hr)TNF or a combination of two overlapping, 24-h continuous infusions of hrIFN-gamma and hrTNF were analyzed for IL-6 in a sensitive bioassay. A transient appearance of circulating IL-6 was observed with peak levels between 3 and 6 h after the start of the hrTNF infusion. These peak levels correlated quite well with the dose of hrTNF administered (r = 0.86; p less than 0.001). The maximal value observed was 27.5 ng/ml IL-6 in a sample of a patient receiving 545 micrograms/m2 hrTNF. The combination of hrIFN-gamma (200 micrograms/m2) and hrTNF in the infusions resulted in higher IL-6 levels than a comparable dose of hrTNF alone. A maximal value of 23.5 ng/ml IL-6 was observed in a patient receiving 205 micrograms/m2 hrTNF. No IL-6 was found in the plasma of patients during the 12-h infusion with hrIFN-gamma alone, except for two borderline samples.